Amelogenesis imperfecta: A clinician's challenge - V Chamarthi; B R Varma; M Jayanthi (Wolters Kluwer Medknow Publications, 2012)
Defective enamel formation can be explained as defects occurring at the stages of enamel formation. Quantitative defects in matrix formation leads to hypoplastic form of amelogenesis imperfecta. Inadequate mineralization of matrix leads to hypocalcification and hypomaturation variants. The demarcation of matrix formation and mineralization is not so distinct. This paper describes a case of a 7-year-old boy with amelogenesis imperfecta - Type IA i.e., hypoplastic pitted autosomal dominant.